Analyze of Speech Act Used in Tea Commercials: Penelitian - Qurrata ain; Burhanudin Rais (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Advertisements have been an integral part of social culture, acting as a means to showcase brands and connect with consumers. This article intends to examine the speech acts that can generate meaning and have a persuasive impact by comparing the advertisements for Teh Kotak and Teh Botol Sosro. The focus of the study is on the locutionary, illocutionary, and perlocutionary aspects of speech act theory. By analysing these three communication levels, the research aims to understand how representative speech acts relate to the literal message, its purpose, and its effect on the audience. Employing a qualitative descriptive approach, the study finds that while locutionary acts are essential for delivering product information, it is the illocutionary and perlocutionary acts that play a more significant role in influencing consumer choices and building emotional ties to the brand. This analysis underscores the importance of language in tea advertisements and provides insights into how speech acts can engage and persuade viewers.